The Increasing of Students' Listening Skills by Using Total Physical Response (TPR) - Ramadani; Syihabuddin (Sean Institute, 2023)
This study dealt with the increase in students’ listening skills by using Total Physical Response (TPR). This study was conducted on students of Politeknik LP3I Medan. This study aimed to increase the student’s listening skills by using Total Physical Response (TPR). This study conducted qualitative research that described the result of the study. There were 20 students as participants in this study. This study used Classroom Action Research (CAR) to know whether this method was effectively implemented in the listening class and can increase students’ listening skills. To know whether the students’ listening skills increased or not, the researcher used the pre-test and the post-test. A pre-test was conducted to know students’ score results before applying Total Physical Response (TPR). Post-test was conducted to compare the pre-test and the post-test to know the difference between the pre-test and post-test. The result of this study, there was increased students’ listening skills by using Total Physical Response (TPR). The class average scores in the pre-test were 292,5, and when the lecturer implemented Total Physical Response (TPR), the student scores increased to 366,6. It meant Total Physical Response (TPR) positively influenced the students.